Kesenjangan Infrastruktur Dasar dan Dampaknya Pada Kualitas Hidup di Kampung Pemulung Savana Kota Makassar - Arifin, Ibrahim; Ahmad, M.Ridwan Said; Arifin, Zulkifli; Arifin, Ibrahim Ibrahim (Universitas Muhammadiyah Makassar, 2026)
This study analyzes the gap in basic infrastructure in the Pemulung Savana Settlement, Makassar City, and its impact on the quality of life of the community. This research employs a descriptive qualitative method, with data collection techniques including observation, in-depth interviews, and documentation. Data analysis is conducted using a thematic method to identify key problem patterns. The findings reveal that limitations in basic infrastructure such as restricted access to clean water, poor sanitation systems, unstable electricity, and inadequate roads and transportation negatively affect the well-being of the community. The lack of educational and healthcare facilities worsens socio-economic conditions, leading to low health levels and limited educational opportunities for children. The absence of essential services also increases the risk of disease and exacerbates poverty. Furthermore, the unclear land ownership status hinders infrastructure improvement efforts. These findings highlight that infrastructure disparities in marginal areas require serious attention from various stakeholders to develop inclusive and sustainable solutions. Improving access to basic services and implementing more equitable development policies are essential to enhancing the quality of life in the area.